Current progress, challenges and perspectives in microalgae-based nutrient removal for aquaculture waste: A comprehensive review. (20th December 2020) - Nie, Xifan; Mubashar, Muhammad; Zhang, Shi; Qin, Yufeng; Zhang, Xuezhi
Abstract: The increase in nutrients in aquaculture waste and their adverse environmental impacts has led to interest in adopting more efficient, cost-effective wastewater treatment methods as alternatives to conventional processes. The phytoremediation of aquaculture wastewater with microalgae has great potential due to its high nutrient removal efficiency and low cost. Most importantly, the microalgal biomass can be utilized directly or converted into aquacultural feed. However, the diversity and dynamic changes in wastewater characteristics, light-limited microalgal growth and high harvesting costs are still challenges to its successful application. This review gives an extensive overview of microalgae-based nutrient removal from aquaculture waste, including the challenges in the development of an efficient treatment system and the factors affecting microalgal growth and nutrient removal. Novel cultivation strategies to enhance biomass productivity and nutrient removal are discussed. Moreover, suggestions are proposed for the development of a more robust model for nutrient loading and removal. Graphical abstract: Image 1